2018
DOI: 10.7150/jca.21520
|View full text |Cite
|
Sign up to set email alerts
|

Modulated electro-hyperthermia induced loco-regional and systemic tumor destruction in colorectal cancer allografts

Abstract: Background: Modulated electro-hyperthermia (mEHT), a non-invasive intervention using 13.56 MHz radiofrequency, can selectively target cancers due to their elevated glycolysis (Warburg-effect), extracellular ion concentration and conductivity compared to normal tissues. We showed earlier that mEHT alone can provoke apoptosis and damage associated molecular pattern (DAMP) signals in human HT29 colorectal cancer xenografts of immunocompromised mice.Materials: Here we tested the mEHT induced stress and immune resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
86
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(98 citation statements)
references
References 28 publications
6
86
2
Order By: Relevance
“…Open access the ubiquitin-specific peptidase inhibitor spautin-1, the antibiotic bleomycin, the protein phosphatase-2A inhibitor LB-100, the Chinese herbal medicine component shikonin and capsaicin [34][35][36][37][38] and (8) numerous physical interventions, encompassing various forms of ionizing radiation, extracorporeal photochemotherapy, hypericinbased photodynamic therapy (PDT), near-infrared photoimmunotherapy, high hydrostatic pressure, severe cytotoxic heat shock, nanopulse stimulation and electrohyperthermia. [39][40][41][42][43][44][45][46][47][48][49] Importantly, dose and administration schedules have a major impact on the ability of many of these agents to initiate productive ICD. [50][51][52] The aforementioned ICD inducers have been instrumental not only for identifying the molecular machinery that underlies the immunogenicity of some variants of RCD, 5 but also for elucidating the pathophysiological and therapeutic implications of the process.…”
Section: Introductionmentioning
confidence: 99%
“…Open access the ubiquitin-specific peptidase inhibitor spautin-1, the antibiotic bleomycin, the protein phosphatase-2A inhibitor LB-100, the Chinese herbal medicine component shikonin and capsaicin [34][35][36][37][38] and (8) numerous physical interventions, encompassing various forms of ionizing radiation, extracorporeal photochemotherapy, hypericinbased photodynamic therapy (PDT), near-infrared photoimmunotherapy, high hydrostatic pressure, severe cytotoxic heat shock, nanopulse stimulation and electrohyperthermia. [39][40][41][42][43][44][45][46][47][48][49] Importantly, dose and administration schedules have a major impact on the ability of many of these agents to initiate productive ICD. [50][51][52] The aforementioned ICD inducers have been instrumental not only for identifying the molecular machinery that underlies the immunogenicity of some variants of RCD, 5 but also for elucidating the pathophysiological and therapeutic implications of the process.…”
Section: Introductionmentioning
confidence: 99%
“…The SAR distribution follows the thermal and electromagnetic heterogeneity of the malignant tissue, resulting in higher absorbance in the cancer than in the surrounding normal issue [ 27 , 28 ]. The general feature of tumor destruction using in vivo mEHT models was the extended morphological tumor damage, starting as early as after 24 h in the middle of the treated tumor lamps, which then almost evenly spread from inside to the periphery ( Figure 1 c) [ 11 , 12 ]. This suggested the instant penetration, concentration, and enhanced energy absorption in the middle of tumors.…”
Section: Standardized Meht Treatment and Protocolsmentioning
confidence: 99%
“…SzIE, ÁOTK MÁB 26/2013 and the most recent one, no. PE/EA/633-5/2018), using mouse C26 colorectal cancer cell line allografted into BALB/c mice, are found in Vancsik et al, 2018 and 2019 [ 12 , 29 ]. In the studies, 10% neutral-buffered, formalin-fixed tumor tissues embedded in paraffin were cut for 2–3 µm thick serial sections and mounted on silanized adhesion glass slides.…”
Section: Standardized Meht Treatment and Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical research suggests that mEHT combined with immunotherapies is able to elicit an immune-mediated response (13) which may even extend to untreated tumors. Vancsik et al showed that mEHT induced DAMPs in murine models was followed by an invasion of antigen presenting cells (APC) and T-cells at the site of the treated tumor and that when mEHT was administered combined with a T-cell stimulating agent, APC and T-cell invasion was also seen in the untreated tumors of the same murine model (14). In an in vivo study, mEHT combined with dendritic cell therapy elicited a response to untreated tumors in murine squamous cell carcinoma (SCCVII) models (15).…”
Section: Introductionmentioning
confidence: 99%